Twelve‐Month results from multicenter, open‐label, randomized controlled clinical trial comparing differential target multiplexed spinal cord stimulation and traditional spinal cord stimulation in subjects with chronic intractable back pain and leg pain. Issue 8 (27th August 2021) - Fishman, Michael; Cordner, Harold; Justiz, Rafael; Provenzano, David; Merrell, Christopher; Shah, Binit; Naranjo, Julian; Kim, Philip; Calodney, Aaron; Carlson, Jonathan; Bundschu, Richard; Sanapati, Mahendra; et al.
Abstract: Background: Spinal cord stimulation (SCS) is a well‐established treatment for chronic intractable pain of the trunk and/or limbs; however, low back pain (LBP) is difficult to treat using traditional SCS. Differential Target Multiplexed spinal cord stimulation (DTM SCS) is an advanced approach inspired from animal studies demonstrating improved pain‐related behavior and pain‐relevant biological processes. Objective: The purpose of this study was to compare the effectiveness of DTM SCS and traditional SCS in treating chronic LBP and leg pain (LP). Methods: This prospective, postmarket randomized controlled trial compared DTM SCS to traditional SCS in patients with chronic LBP and LP. Primary end point was LBP responder rate (percentage of subjects with ≥ 50% relief) at 3 months. Noninferiority and superiority were assessed. Other outcomes included mean change in back and leg pain, responder rates, disability, global health, satisfaction, and safety profile throughout the 12‐month follow‐up. Results: One hundred twenty‐eight subjects were randomized across 12 centers (67 DTM SCS and 61 traditional SCS). Of the 94 patients implanted, 46 subjects in each group completed the 3‐month assessment. LBP responder rate of 80.1% with DTM SCS was superior to 51.2% with traditional SCS ( p  = 0.0010). Mean LBP reduction (5.36 cm) with DTM SCS was greater than reduction (3.37 cm) with traditional SCS ( p  < 0.0001). These results were sustained at 6 months and 12 months. Safety profiles were similar between treatment groups. Conclusion: Superiority of DTM SCS compared with traditional SCS for chronic LBP was demonstrated. Clinical improvements provided by DTM SCS were sustained over 12 months and are expected to significantly impact the management of chronic LBP.